PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - marita aldiana (Jurnal Akuntansi Indonesia, 2019)
This research's purpose was to find out the influence of corporate social responsibility disclosure, leverage, profitability and firm size on earnings management. Variable corporate social responsibility disclosure measured using the Corporate Social Responsibility Index (CSRI). Leverage measured using the debt ratio. Profitability measured using Return on Assets (ROA). Firm size measured using the logarithm of total assets. While the earnings management variables were measured using discretionary accruals. Population in this research are all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2016-2017. Sampling technique using purposive sampling method. After the selection, there are 151 samples that meet the criteria. The analytical methods used is descriptive statistics, classical assumption test (normality test, heteroscedasticity, multicolinearity and autocorrelation) and hypothesis testing. Based on the analysis, it is shown that leverage influence earnings management. While corporate social responsibility disclosure, profitability, and firm size do not influence earnings management.